العوامل المؤهبة لنقص وزن الولادة - عثمان منير; الحكيم أمل; الزازا حسين (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة لتقصي العوامل المؤهبة لنقص وزن الولادة والوقوف على الدور الحقيقي لكل منها. شملت الدراسة 202 حالة تم تقسيمها إلى مجموعتين: مجموعة الولدان ناقصي وزن الولادة (LBW) وشملت 112 وليدا أوزانهم تساوي أو تقل عن 2500 غ، ومجموعة الشاهد ، وهي مجموعة من الولدان الطبيعيين أوزانهم تزيد عن 2500 غ وعددهم 90 وليدا وتمت المقارنة بين المجموعتين. - بلغ عدد الولدان ناقصي وزن الولادة بتمام الحمل 44 وليدا أي بنسبة 39.28% من حالات الدراسة بينما بلغ عدد الخدج تحت (37 أسبوعا حمليا) 68 خديجا وشكلوا نسبة 60.72 % من مجموعة الدراسة. أما في مجموعة الشاهد فكان لدينا 6 خدج فقط أي بنسبة 6.6% فقط. - لوحظ زيادة نسبة LBW عند الأمهات تحت عمر 18 سنة حيث كانت نسبتهم 2.6% مقابل 1.1% في مجموعة الشاهد. - ظهر دور لترتيب الحمل في الـ LBW فكانت نسبة LBW إذا كان الحمل هو الأول42.8 % مقابل 34.4% في مجموعة الشاهد، وإذا كان الحمل هو الخامس وما فوق فالنسبة 10.7 % مقابل 7.7 للشاهد. - تزداد هذه النسبة إذا كانت الفترة الفاصلة عن الحمل السابق أقل من سنة (24% مقابل 5.5%) فقط للشاهد. - كانت نسبة القرابة بين الأبوين (درجة أولى) 25% في مجموعة LBW مقابل 14.4 % في مجموعة الشاهد. - كانت نسبة دخل الأٍسرة الضعيف جداً 22.3 % في مجموعة LBW مقابل 6.6% في مجموعة الشاهد. - كانت نسبة سوء تغذية الأم 13.4% في مجموعة LBW مقابل 6.6 %في مجموعة الشاهد. - ظهر للتدخين دور فكانت نسبة الأمهات المدخنات 19% مقابل 15.5 % في مجموعة الشاهد. - وعند دراسة دور الكافئين كانت نسبة اللواتي تناولن أكثر من فنجانين قهوة باليوم 17% مقابل 12.2% للشاهد. - بلغت نسبة التوائم في مجموعة LBW 21.4% مقابل 1.11 % في مجموعة الشاهد. - بلغت نسبة ارتفاع الضغط في مجموعة LBW 8.9% مقابل 6.6% في مجموعة الشاهد. - كان للشدات أثناء الحمل (جسدية ونفسية) دور كبير فكانت بنسبة 30% مقابل 10% في مجموعة الشاهد - نسبة الانتانات البولية والتناسلية في مجموعة LBW 38.4% مقابل 34.4% في مجموعة الشاهد. - نسبة النزوف التناسلية في مجموعة LBW 27.6% مقابل 6.6 % في مجموعة الشاهد. - نسبة اضطرابات المشيمة في مجموعة LBW 12.5 % مقابل 6.6 % في مجموعة الشاهد. - نسبة انبثاق الأغشية الباكر في مجموعة LBW 25.9% مقابل 7.7 % في مجموعة الشاهد. This study was performed to invistigate the predisposing factors to low birth weight, and discover the real role of each one. The study included 202 cases, which were divided in to two groups: 1- low birth weight Newborns (LBW) and they were 112 those weight was equal or less than 2500 g. 2- Control group “Normal” Newborns” and their weight was more than 2500 gr and their number was 90 newborn. And we have compared between the two groups: - The number of full term newborns with low birth weight was 44 case with percentage of 39.28% from the first group. While the number of preterm newborns (gestational age under 37 weeks) was 68 and they made a percentage of 60.72% from the first group whereas in the control group there was 6 preterm newborn only with a percentage of 6.6 % only. - We have noted an increase in the percentage of LBW with maternal age less than 18 years and the percentage was 2.6 % while 1.1 % in the control group. - The serial number of the gestation was noted as a predisposing factor to LBW, in the first gestation the percentage was 24.8% while 34.4% in the control group, and in the fifth and later gestation on the percentage was 10.7% while 7.7 % in the control . - The percentage of LBW increases in the presence of previous LBW infant (13.4 % while 7.7% in control) - The inter pregnancy interval less than 1 year increases the percentage (LBW) (24% while 5.5 %) . - The presence of kinship between the parents (first degree) was in 25% LBW group and 14.4% in control. - Very low socieoeconomic level of the family was noted 22.3 % in LBW group and 6.6% in control. - Malnorishment of the mother was in 13.4 % of LBW group and 6.6 % in control. - Smoking ciggarettes was noted as a factor that leads to LBW newborn with a percentage 19% while 15.5 % in control group. - Drinking two cups of coffee daily increases the risk of LBW with percentage 17% while 12.2 % in control. - the percentage of twin gestation in LBW was 21.4% while 1.11 % in control. - The percentage of maternal hypertension was 8.9% while 6.6 % in control. - Psychogenic and somatic stress during pregnancy, played a major role in LBW with a percentage of 30% while 10% in control group. - Maternal genitourinary tract infections increases LBW percentage 38.4% while 34.4% . - Genital hemorrhage increases the percentage of LBW 27.6% while 6.6 % in control. - The percentage of placental disorders was 12.5% in LBW while 6.6% in control . - The percentage of premature rupture of membranes was25.9% in LBW while 7.7 in control.